Developing enjoyable second language learning software tools: A computer game paradigm - Ang, Chee Siang; Zaphiris, Panayiotis (My University, 2009)
This chapter attempts to examine computer game theories ludology and narratology that explain computer games as play activities and storytelling media. Founded on this theoretical explanation, a game model that incorporates gameplay and narratives is presented. From the model, two aspects of learning in game environment are identified: gameplay-oriented and narrative-oriented. It is believed that playing computer games involves at least one of these types of learning, thus this games nature can be utilized in designing engaging educational software. In addition, based on Malones theoretical framework on motivational heuristics, it is found out that there are two methods of applying computer games in language learning: extrinsic and intrinsic, depending on the integration of game designs and learning materials. Then, two cases of language learning games are scrutinized using the game model in order to demonstrate the use of computer games in language learning.
Keywords: Case Study; Computer-Assisted Education; Computer Games; Educational Multimedia; Educational Technology; Electronic Learning; Exploratory Study; Interactive Technology; Interface; Language Learning; Ludology; Multimedia Application; Narratology; Technology Mediated Learning